2020
DOI: 10.1002/jcla.23399
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA NEAT1 serves as a novel biomarker for treatment response and survival profiles via microRNA‐125a in multiple myeloma

Abstract: Background The present study aimed to explore the association of long non‐coding RNA nuclear paraspeckle assembly transcript 1 (lncRNA NEAT1) with multiple myeloma (MM) risk and further investigate its correlation with clinical features, treatment response, survival profiles, and its interaction with microRNA‐125a (miR‐125a) in MM patients. Methods Totally, 114 de novo symptomatic MM patients and 30 healthy donors (as controls) were recruited. Their bone marrow samples were collected before treatment (MM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In this study, lncRNA NEAT1, as mentioned before, is also involved in the pathological development of diseases. A study found that lncRNA NEAT1 could be used as a biomarker of multiple myeloma, and myeloma cells could inhibit the differentiation of BMSCs into osteoblasts [ 27 ]. Overexpression of NEAT1 has also been shown to promote osteoclast formation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lncRNA NEAT1, as mentioned before, is also involved in the pathological development of diseases. A study found that lncRNA NEAT1 could be used as a biomarker of multiple myeloma, and myeloma cells could inhibit the differentiation of BMSCs into osteoblasts [ 27 ]. Overexpression of NEAT1 has also been shown to promote osteoclast formation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the cell- and tissue- specificity of lncRNAs, showing that their deregulation—and thus, their potential function—needs to be addressed in each tumor. For example, MALAT1 (one of the most widely studied lncRNAs [ 103 ]) and NEAT1 are able to bind or interfere with different molecules and pathways depending on the tissue or disease ( Table 1 ) [ 77 , 106 ]. MALAT1 acts as an miRNA sponge binding to miR-1271-5p ( Figure 1 ), miR-181a-5p and miR-509-5p in MM, to miR-195 in HCC or to miR-206 and miR-363-3p in gallbladder cancer [ 63 , 65 , 66 , 67 , 68 ].…”
Section: Role Of Lncrnas In the Pathobiology Of MMmentioning
confidence: 99%
“…MALAT1 acts as an miRNA sponge binding to miR-1271-5p ( Figure 1 ), miR-181a-5p and miR-509-5p in MM, to miR-195 in HCC or to miR-206 and miR-363-3p in gallbladder cancer [ 63 , 65 , 66 , 67 , 68 ]. In the case of NEAT1 , it binds to miR-125a in MM and to miR-193a-3p in lung adenocarcinoma, among others [ 77 , 106 ]. Usually, the expression of lncRNAs and miRNAs is negatively correlated.…”
Section: Role Of Lncrnas In the Pathobiology Of MMmentioning
confidence: 99%
See 2 more Smart Citations